What induces online loyalty? Online versus offline brand images - Kwon, Wi-Suk; Lennon, Sharron J. (Journal of business research, 2009)
This study investigates the effect of the interplay between a multi-channel retailer's offline and online brand images on consumers' online perceived risk and online loyalty within the framework of a theory of cognitive dissonance. A sample of 671 female college students participated in an experiment using a 2 (prior offline brand image) × 2 (online performance) between-subjects design. Results reveal that offline brand image exerts significant effects on online brand image – which, in turn, significantly explains online perceived risk – and online customer loyalty. However, online perceived risk has no significant effect on online customer loyalty after controlling for the effects of online and offline brand images. These results provide implications for the direct and indirect halo effects of offline brand image and the direct effect of online performance that may influence consumers' perceptions, expectations, and loyalty regarding multi-channel retailers.